The just city - Fainstein, Susan S. (Cornell University Press, 2010)
Introduction : toward an urban theory of justice -- Philosophical approaches to the problem of justice -- Justice and urban transformation : planning in context -- New York -- London -- Amsterdam : a just city? -- Conclusion : toward the just city